"Low Profile" or Entrepreneurial? Gender, Class, and Cultural Adaptation in the Global Microfinance Industry. (October 2015) - Radhakrishnan, Smitha
Highlights: Microfinance training programs emerge from global development discourse. The class and organizational position of development actors affects implementation. "Official" and "unofficial" forms of cultural adaptation collide within a program. Commercialization of microfinance does not produce accountability to clients. Organizational tensions prevent actors from attending to client interests. Summary: This study examines how discourses of entrepreneurial womanhood, filtered through a chain of hierarchically positioned actors in global microfinance, translate into interactions with borrowers. Drawing from ethnography, interviews, and document analysis on a set of entrepreneurial trainings delivered to nonentrepreneurial borrowers in urban India, this study argues that parallel, conflicting processes of cultural adaptation within the organization, and tensions between various actors, create an environment in which there is no incentive to cater to the interests of working class clients. Commercialized microfinance, thus, may not necessarily produce accountability to client interests.